Low-Temperature and Low-Pressure Cu–Cu Bonding by Highly Sinterable Cu Nanoparticle Paste - Junjie Li; Xing Yu; Tielin Shi; Chaoliang Cheng; Jinhu Fan; Siyi Cheng; Guanglan Liao; Zirong Tang (Nanoscale Research Letters, 2017)
Abstract A reliable Cu–Cu bonding joint was achieved by using the highly sinterable Cu nanoparticle paste. Pure copper nanoparticles used in the preparation of nanoparticle paste were synthesized through simple routes, with an average size of 60.5 nm. Under an Ar-H2 gas mixture atmosphere, the Cu nanoparticle paste exhibited large areas of fusion after sintering at 300 °C and reached a low electrical resistivity of 11.2 μΩ cm. With the same temperature as sintering, a compact Cu–Cu bonding joint was achieved under the pressure of 1.08 MPa and the shear strength of the joint could achieve 31.88 MPa. The shear strength and the elemental composition of the bonded joint were almost unchanged after aging test, which proves that the Cu–Cu bonding with this process has excellent thermal stability.